2021
DOI: 10.1002/agt2.108
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots: An innovative luminescent nanomaterial

Abstract: In recent years, carbon dots (CDs), including carbon nanodots, carbonized polymer dots, carbon quantum dots, and graphene quantum dots have attracted a mounting interest as readily accessible, nontoxic, and relatively inexpensive carbon-based nanomaterials. Yet, despite intense research for a number of years, a unifying picture is still lacking to clarify the exact definition, clear chemical structure, and unique optical properties of this family of nanomaterials. In this review, we systematically summarize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 196 publications
(344 reference statements)
0
55
0
Order By: Relevance
“…The synthetic approaches are generally classified into two main categories: top-down and bottom-up. [45][46][47]…”
Section: Preparation Of Cdsmentioning
confidence: 99%
“…The synthetic approaches are generally classified into two main categories: top-down and bottom-up. [45][46][47]…”
Section: Preparation Of Cdsmentioning
confidence: 99%
“…The authors showed that these pink fluorescent CDs can be applied for cancer cell bioimaging, antibacterial activity, and ROS scavenging. Another new topic regarding biomedical application of CDs is related to covering all spectral regions, particularly the near-infrared region [ 59 – 62 ]. Nevertheless, despite all these promising applications of CDs, to date, it is necessary to establish an effective large-scale production synthesis method, standardize the composition and structure of CDs, and achieve a better yield [ 63 – 69 ].…”
Section: Carbon Dotsmentioning
confidence: 99%
“…Nevertheless, despite all these promising applications of CDs, to date, it is necessary to establish an effective large-scale production synthesis method, standardize the composition and structure of CDs, and achieve a better yield [ 63 – 69 ]. In addition, a better comprehension of the nature of the photoluminescence properties is needed [ 59 , 70 ]. Li et al [ 71 ] reported and interestingly achieved the large-scale production of CDs by an aldol condensation reaction at room temperature and ambient pressure.…”
Section: Carbon Dotsmentioning
confidence: 99%
“…In recent years, CDs with solid-state emission were continuously reported. 24,25 Control and modification of surface electronic states are of significance for realizing the solid-state emission of CDs. In a CPDs system, the polymer's frameworks or cross-linked networks can preclude the rotational motions of fluorophore dots inside, realizing cross-linking-induced solid emission of CPDs.…”
Section: Structural and Surface Characteristics Of Carbon Dotsmentioning
confidence: 99%